2021
DOI: 10.1177/0885412220986421
|View full text |Cite
|
Sign up to set email alerts
|

City Light or Star Bright: A Review of Urban Light Pollution, Impacts, and Planning Implications

Abstract: Light pollution (LP) is a growing scourge in metropolitan areas yet is largely ignored by planners. It has negative impacts on the health of humans and of wildlife and threatens views of the night sky. This article reviews adverse impacts in multiple categories, highlights mitigation strategies, and makes the case for more engagement in planning scholarship and practice especially in the United States. Defining LP and balancing competing values in its mitigation are political acts, challenged by, among other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 75 publications
(128 reference statements)
0
10
0
1
Order By: Relevance
“…Along with the development of urban infrastructures, in addition to street lighting, other light sources appeared, increasing the brightness of the sky glow. Light pollution is mainly due to the operation of wrongly designed street lighting, advertising, illumination of sports stadiums, construction, security, and façade lighting [7][8][9][10][11]. To this day, there is no real effective policy that deals with this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the development of urban infrastructures, in addition to street lighting, other light sources appeared, increasing the brightness of the sky glow. Light pollution is mainly due to the operation of wrongly designed street lighting, advertising, illumination of sports stadiums, construction, security, and façade lighting [7][8][9][10][11]. To this day, there is no real effective policy that deals with this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Human influence is one of the main drivers of landscape change and loss of biodiversity [48,49]. Nighttime light pollution caused by humans has influenced the physiological and behavioral pattern of organisms, and thus threatened biodiversity, but it has been persistently ignored in macroecology and ecological connectivity research [50,51]. We found that the matrix in our study area was significantly disrupted by nighttime light.…”
Section: Discussionmentioning
confidence: 74%
“…Table A2. Overview of terminologies and definitions of responses to light in living organisms and ecosystems [53,[291][292][293][294][295][296][297][298][299].…”
Section: Electric Electric Lightingmentioning
confidence: 99%
“…The visual sensitivity of a vertebrate to see when exposed to conditions such as twilight at luminances between 0.01 and 3 cd/m 2 . Mesopic vision involves both photoreceptors (rods and cones) for scotopic and photopic vision [53,298].…”
Section: Mesopic Visionmentioning
confidence: 99%
See 1 more Smart Citation